Corporate Debt Overhang and Investment Firm-Level Evidence - Borensztein, Eduardo (World Bank E-Library Archive, 2018)
This paper investigates empirically the linkages between corporate debt overhang and investment activity at the firm level for a cross section of large-sized emerging market and developing economies. It analyzes the extent to which investment may be discouraged by high levels of debt that put at risk future profits, as well as firm dimensions that may sharpen the debt-investment link. Using balance sheet data from a broad set of emerging market and developing economy firms, the analysis suggests that corporate debt overhang imposes a sizable effect on investment at the firm level. This linkage is more pronounced for large firms and highly leveraged firms. The analysis also finds evidence of a nonlinear effect, in which debt overhang discourages investment more severely under high levels of indebtedness